A Novel Approach to Pharmacy Practice Law Instruction - Matthew Deneff; Lisa M. Holle; Jill M. Fitzgerald; Kathryn Wheeler (MDPI AG, 2021)
Pharmacy law instruction is often taught as a didactic course; however practical application of pharmacy law is a main component of pharmacy practice. Technology-based simulations are becoming more frequently used to enhance didactic pharmacy education. The goal of this study was to evaluate the utility of and student perceptions on the usefulness of MyDispense community pharmacy simulation for additional law instruction that if successful might prompt curricular revamping. This Institutional Review Board-approved, two-year, qualitative, prospective, survey study was conducted in a case study class where students completed MyDispense exercises focused on common legal issues that arise in practice, both individually before and within groups during class. Participating students completed a qualitative survey directed at use of MyDispense for pharmacy law review, which included a series of close-ended questions graded on a Likert scale and open-ended questions thematically grouped. Thirty-eight (41%) and twenty-eight (31%) students completed surveys in 2017 and 2018, respectively. The majority of respondents felt exercises improved their understanding of pharmacy laws, focused on challenging areas, and were more interesting than additional lectures. However, certain topics were reported as irrelevant based on practice experiences or not ideal for simulation, and students desired exercises on state laws versus pharmacy policies. Students reported the MyDispense simulation exercises helped them to recall pharmacy laws and focus on topics that were challenging. These study results prompted curricular revamping to incorporate MyDispense throughout the curriculum for practice in recognizing and solving legal scenarios, along with didactic course changes.